(untitled) (ENTHYMEMA, 2022)
The article proposes a reflection on the category of “transnationalism,” of historical and sociological derivation, in order to grasp the opportunities of its use in the field of theory of literary comparatistics. In particular, some central themes of the history of the discipline, such as “world literature” and the “canon,” are called into question, which in the light of the transnational dimension—not to be confused with the international one—open up to new declinations and to the changed literary landscapes of contemporaneity.